Wpływ odłogowania na właściwości gleb, obszaru dorzecza środkowej Odry = The influence of fallowing on soil properties in middle basin area of the Odra - Łętkowska, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the work was to define the way of soils using on physical-chemical and chemical properties of arable and fallowed soils. The object of investigations were soils in middle bas in area of the Odra with various time of fallowing. Selected objects differed in type of solis: river alluvial soils, rusty soils, gley soils and soils lessives.
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)